Family firm’s heterogeneity and firm risk - Lisboa, Inês (2018)
The behavioral agency theory suggests that family firms present less risk than non-family firms to protect their socioemotional wealth. Most studies analyzing this field focus on the bank sector or the US economy. This study aims to examine whether there are differences in risk between family and non-family firms using Portuguese listed firms during fourteen years. Moreover we provide new evidence taking into account firms’ heterogeneities. Family and non-family firms are not homogeneous groups and the firm’s growth opportunities, age and size can be moderators of the relationship between family control and firm risk. We also analyze the effect on risk of family control using family ownership and the F-PEC scale. Our overall results strongly evidence that firms’ heterogeneities play an important role in firm’s risk exposure. These findings are relevant for institutional and individual investors as well as for the professional managers of these firms.